Singular levels and topological invariants of Morse–Bott foliations on non-orientable surfaces - Martínez-Alfaro, José; Meza-Sarmiento, Ingrid S. [UNESP]; Oliveira, Regilene D. S. (Uniwersytet Mikolaja Kopernika/Nicolaus Copernicus University, 2018)
We investigate the classification of closed curves and eight curves of saddle points defined on non-orientable closed surfaces, up to an ambient homeomorphism. The classification obtained here is applied to Morse–Bott foliations on non-orientable closed surfaces in order to define a complete topological invariant.
Keywords: Bott functions; Foliations; Morse; Non-orientable surfaces; Topological invariants